2018
DOI: 10.1093/jas/skx031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of differently processed yeast (Kluyveromyces fragilis) on feed intake and gut physiology in weaned pigs

Abstract: Two feeding trials were conducted to investigate the effects of hydrolyzed (HY) or non-hydrolyzed (NHY) yeast (Kluyveromyces fragilis) in isoenergetic and isonitrogeneous diets in the postweaning period. In experiment 1, a total of 550 unsexed pigs (6.5 ± 0.5 kg BW), weaned at 24 ± 2 d of age, were allocated to five treatment groups, receiving either a control diet (CON) or diets with 1%, 3%, and 5% HY (groups HY1, HY3, and HY5, respectively), or a diet with 3% NHY (group NHY3). In experiment 2, a total of 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Our results are supported by Keimer et al [6] that the digestibility of CP and E tended to increase in 1.0% hydrolyzed yeast group. We speculate that the healthy morphology of the intestine was improved by diet with added YH.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are supported by Keimer et al [6] that the digestibility of CP and E tended to increase in 1.0% hydrolyzed yeast group. We speculate that the healthy morphology of the intestine was improved by diet with added YH.…”
Section: Discussionsupporting
confidence: 91%
“…We speculate that the healthy morphology of the intestine was improved by diet with added YH. Håkenåsen [11] researched that fecal DM was linearly increased after adding levels of yeast, meanwhile, Keimer et al [6] showed that weaned pigs had significantly increased villus height, villus/crypt ratio in jejunum, and reduced crypt depth in the colon when fed a diet with added 1% hydrolyzed yeast. Carlson [27] has more detailed observations that after being fed a yeast diet, nursery pigs had shorter crypt depths which means that fewer cells were migrating to the villus to ad digestion and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the adsorption of AFB 1 using yeast CW (JOANNIS CASSAN et al 2011). YIANNIKOURIS et al (2006) found that 6177 µg/mL were adsorbed per 100 µg/mL of CW. PEREYRA et al (2012) studied the adsorption of AFB 1 with CW of commercial yeasts applying mathematical models to explain the type of interaction of the toxin with the adsorbent that occurred.…”
Section: Wall Cell Yeast As An Aflatoxin B 1 Adsorbentmentioning
confidence: 99%
“…DEVEGOWDA and CASTALDO (2000) explained that the interaction of AFB 1 with the CW is from mannan glucans through hydrogen bonds. YIANNIKOURIS et al (2006) showed that the interaction with mycotoxins is due to the helical conformation of 1-3 β glucans in the complexation of ZEN, AFB 1 , DON and PAT. The 1-3 β glucans participate in Van der Waals unions and hydrogen bonds, while 1-6 β glucans strengthen Van der Waals unions and stabilize the interaction.…”
Section: Wall Cell Yeast As An Aflatoxin B 1 Adsorbentmentioning
confidence: 99%
See 1 more Smart Citation